Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Pada Bengkel Adi Service Samarinda - Nurfitriani 3, Mahfud 1, Mardiana 2 (EKONOMIA, 2021)
The purpose of this study is : 1.) To find out the reliability effect the customer satisfaction at the Samarinda Adi Service workshop. 2.) To find out responsiveness effect the customer satisfaction at Samarinda Adi Service workshop. 3.) To find out the assurance effect on customer satisfaction at Samarinda Adi Service workshop. 4.) To find out empathy effect customer satisfaction at the Samarinda Adi Service workshop. 5.) To find out tangible effect customer satisfaction at Samarinda Adi Service workshop. 6.) To find out the price effect on customer satisfaction at Samarinda Adi Service workshop. 7.) To find out the reliability, responsiveness, assurance, empathy, tangible and price together effect customer satisfaction at the Samarinda Adi Service workshop. The theory used in this research is service quality, price and customer satisfaction.This research was conducted at Samarinda Adi Service Workshop. Samples taken as many as 77 respondents with the Probability Sampling method with sampling techniques using Simple Random Sampling. Data collection by distributing questionnaires using a Likert scale to measure each indicator. The analytical tool in the study used multiple linear regression analysis using SPSS v23 statistical program tools.The results showed that : 1.) Reliability variable has a significant effect on customer satisfaction at Samarinda Adi Service Workshop. 2.) Responsiveness variable had no significant effect on customer satisfaction at the Samarinda Adi Service workshop. 3.) Assurance variable has a significant effect on customer satisfaction at the Samarinda Adi Service workshop. 4.) Empathy variable has a significant effect on customer satisfaction at Samarinda Adi Service Workshop. 5.) Tangible variable has a significant effect on customer satisfaction at Samarinda Adi Service Workshop. 6.) Price variable had no significant effect on customer satisfaction at the Samarinda Adi Service workshop. 7.) The variables of reliability, responsiveness, assurance, empathy, tangible and price together have a significant effect on customer satisfaction at the Samarinda Adi Service workshop.